AKTIVITAS ANTIMIKROBA EKSTRAK METANOL BIJI MANGGA HARUM MANIS (Mangifera indica L. Varietas Arumanis 143) TERHADAP Bacillus subtilis dan Shigella flexneri - Tiah Rachmatiah; Masniari Poeloengan; Helgario Pratama (SAINSTECH FARMA, 2011)
Antimicrobial activity of methanol extract from harum manis mango seeds (Mangifera indicaL.varietas Arumanis 143) has been investigated against Bacillus subtilis and Shigella flexneri. Harum manismango seeds powder were extracted with methanol by maceration method Phytochemical screening of theextract indicated that the extract contained flavonoids, saponins and tannins. Antimicrobial activity of theextracts were tested against Bacillus subtilis and Shigella flexneri with amoxicillin as a positive control.Diffusion and dilution methods by using Mueller-Hinton medium.were used in this test. The results exhibitedtha tzone diameters of inhibition of 50% extract solution in water against B.subtilis and S.flexneri wererespectively 18 mm and 17 mm. The Minimum Inhibitory Concentration (MIC) values against B. subtilis andS. flexineri were showed respectively at 0.3% and 3% extract solutions of harum manis mango seeds.